2006
DOI: 10.1108/09653560610654310
|View full text |Cite
|
Sign up to set email alerts
|

A snapshot of the 2004 Indian Ocean tsunami: societal impacts and consequences

Abstract: PurposeThe purpose of this paper is to explore the societal impacts and consequences of the December 26, 2004 Indian Ocean tsunami.Design/methodology/approachOne month after the tsunami, a group of social science researchers from the Disaster Research Center, University of Delaware, and the Emergency Administration and Planning Program, University of North Texas, participated in an Earthquake Engineering Research Institute reconnaissance team, which traveled to some of the most affected areas in India and Sri … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 4 publications
1
34
0
Order By: Relevance
“…This is in line with the findings of Rodriguez et al, (2006) who reported that Tsunami affected Agricultural labourers have been left out of the proposed relief packages offered by the government.…”
Section: Social Constraintssupporting
confidence: 91%
See 1 more Smart Citation
“…This is in line with the findings of Rodriguez et al, (2006) who reported that Tsunami affected Agricultural labourers have been left out of the proposed relief packages offered by the government.…”
Section: Social Constraintssupporting
confidence: 91%
“…Rodriguez et al, (2006) reported that "in some instances, NGOs duplicated efforts or provided assistance not suited to the locale or to the varying population sizes.…”
Section: Personal Constraintsmentioning
confidence: 99%
“…Going beyond an extreme event, we define an extreme context as an environment where one or more extreme events are occurring or are likely to occur that may exceed the organization's capacity to prevent and result in an extensive and intolerable magnitude of physical, psychological, or material consequences to-or in close physical or psycho-social proximity to-organization members. 4 Examples include the Mann Gulch (Weick, 1993) and South Canyon fires (Useem, Cook, & Sutton, 2005), Indian Ocean Tsunami (Athukorala & Resosudarmo, 2005;Rodriquez, Wachtendorf, Kendra, & Trainor, 2006), Bhopal Chemical release (Bowman & Kunreuther, 1988;Shrivastava, 1987;Union Carbide Report, 1985), Three Mile Island meltdown (Hopkins, 2001;Perrow, 1997), Columbia Space Shuttle explosion (Heimann, 1993;Starbuck & Miliken, 1988;Vaughan, 1996), Westray mine disaster (Hynes & Prasad, 1997), Mount Everest climbing incidents (Kayes, 2004;Tempest, Starkey, & Ennew, 2007), hurricane Katrina (Comfort, 2007;Gheytanchi et al, 2007;Kapucu & Van Wart, 2006;Rego & Garau, 2007), Tenerife airplane collision (Weick, 1990), Chernobyl (Hohenemser, Deicher, Ernst, Hofsäss, Lindner, & Recknagel (1986)), numerous military leadership and combat studies (e.g., Cosby et al, 2006;Morath, Ccurnow, Cronin, Leonard, & McGonigle, 2006;Leonard, Polich, Peterson, Sorter, & Moore, 2006;Department of the Army, 1950Scales, 2006;Snook, 2000;Ulmer, Shaler, Bullis, DiClemente, & Jacobs, 2004;Wong, Bliese, & McGurk, 2003) and organizational doctrine such as the U. S. Army (Department of the Army, 2006) and National Wildfire Service (2007) leadership manuals.…”
Section: Defining Extreme Events and Extreme Contextsmentioning
confidence: 99%
“…A safe environment has a great impact on the perceived safety of an individual, and thus affects their psychological sense of safety. Those victims who are able to retreat to a safer environment prior to, or during the disaster will fare better over time (Rodriguez, Wachtendorf, Kendra, & Trainor, 2006). If safety is not established, the sense of threat will be exaggerated and it will prevent a psychological return to safety (Hobfoll et al, 2007).…”
Section: Sense Of Safetymentioning
confidence: 99%
“…After the Indian Ocean Tsunami, fishermen were unable to work and provide for their families. This change in responsibility of care contributed greatly to the inability of those individuals to feel safe and secure, disrupting the establishment of emotional regulation (Rodriguez et al, 2006). This is why the establishment of a preexisting infrastructure is essential when developing a disaster mental health response plan.…”
Section: Social Support and Connectednessmentioning
confidence: 99%